2020
DOI: 10.1002/admt.202000374
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Functionalization of 3D Printed Polydimethylsiloxane‐Based Microfluidic Devices Obtained through Digital Light Processing

Abstract: This work reports the preparation and 3D printing of a custom‐made photopolymer based on acrylate‐polydimethylsiloxane (PDMS), for the fabrication of complex‐shaped 3D printed microfluidic chips. By selecting and combining the proper materials during the preparation of the resins along with the freedom of design of light‐based 3D printers, 3D microfluidic PDMS‐like chips are obtained with excellent optical features, high chemical stability, and good mechanical properties. Furthermore, taking advantage of unrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 66 publications
0
40
0
Order By: Relevance
“…The rotational viscosity was evaluated imposing a shear ramp to the samples and observing their behavior ( Figure 3 a). Pure TRAD presents a Newtonian behavior with an already relatively high viscosity (~1 Pa*s) when compared with other common DLP printable formulations [ 43 , 44 ]. Nevertheless, a viscous monomer can help the shelf-life of the formulations; in our case the filled formulations resulted stable for at least 7 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rotational viscosity was evaluated imposing a shear ramp to the samples and observing their behavior ( Figure 3 a). Pure TRAD presents a Newtonian behavior with an already relatively high viscosity (~1 Pa*s) when compared with other common DLP printable formulations [ 43 , 44 ]. Nevertheless, a viscous monomer can help the shelf-life of the formulations; in our case the filled formulations resulted stable for at least 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…ATR-FTIR analyses were also performed to confirm the efficiency of the cross-linking reaction. The signal peak at 1190 cm −1 , attributable to the double bond of the acrylated silicone, was used to make a comparison between the liquid formulations and the polymers obtained after different irradiation times (from 2.5 s to 10 s) [ 43 ]. Figure 4 a,b, as an example, report the spectra of the pristine silicone–acrylate formulation and for the same formulation containing 1 phr of BN during irradiation (TRAD and 1 BN in Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hashimoto et al [ 157 ] have described an interesting direct ink writing (DIW) 3D printer for dispensing a fast-curing flexible silicone resin on different substrates to create microchannels. Roppolo et al [ 158 ] have reported 3D printing of photopolymer on the basis of PDMS towards fabrication of microfluidic devices, which can offer attractive optical, mechanical, and chemical stability features. There is increasing interest in development of 3D printing approaches that can allow use of multiple materials [ 159 , 160 ], which could be valuable for integrated valves, through a combination of rigid and flexible materials with different shore values, or integrated electrodes for electrochemical detection or fluid driving purposes.…”
Section: Low-volume Productionmentioning
confidence: 99%
“…Various resins were functionalized by adding fillers, and commercial resins were modified to be photocurable by selecting and combining appropriate photoinitiators and light absorbers. [ 29 ] Notably, hydrogels, crosslinked 3D networks of highly hydrophilic polymers, are processable for VP and widely used in sensing applications not only due to their intrinsic excellent flexibility, biocompatibility, and selective permeability, [ 30 ] but also due to the potential of multifunctionalization, including high transparency, conductivity, tunable mechanical properties, and self‐healing ability. [ 31 ] Reasonable configuration allows full use of functional materials and structural materials in providing perception and flexibility.…”
Section: Fabrication Of Sensors Via Vpmentioning
confidence: 99%